Implementing a Flipped Classroom Approach Assisted by Edpuzzle Video Annotations to Improve Students’ Cognitive Abilities on Global Warming Topics - Meilani, Hasna Azka; Rusnayati, Heni; Danawan, Agus (Universitas Islam Negeri Raden Intan Lampung, 2024)
This study was prompted by students’ low cognitive abilities in solving physics problems, particularly those related to global warming. The research aimed to determine the extent to which a flipped classroom strategy assisted by Edpuzzle video annotations could enhance students’ cognitive abilities. A quasi-experimental design with a control group pretest-posttest approach was employed. The sample comprised 70 tenth-grade students from public high schools in Bandung City. Data were collected through essay-based cognitive tests, an instrument assessing the feasibility of video annotation media, and classroom observation sheets. The n-gain formula was used for data analysis. The results showed a moderate improvement in students’ cognitive abilities. Both the video annotation media and the flipped classroom strategy were considered feasible, with nearly all planned activities successfully implemented. Overall, integrating a flipped classroom approach with Edpuzzle video annotations proves effective in improving students’ cognitive abilities on global warming topics.